Yes & no - Cooper, Elisha (Roaring Brook Press, 2021)
"Join a cat and puppy pair through their day--the ups of being fed and romping through grass, and the downs of days that are too short and things that don't go as planned--as they realize that sometimes the very best thing that can happen is just being together."--